Pelatihan Penggunaan Mesin Perajang Tembakau Untuk Masyarakat Gampong Beurandeh Kecamatan Bandar Baru Kabupaten Pidie Jaya - Masykur Masykur; Al Munawir; Herri Darsan; Amsal Irmalis; Fajri Hadi; Firzan Firzan (Jurnal Pengabdian Agro and Marine Industry, 2022)
Beurandeh village is a village in district of Bandar Baru, Pidie Jaya Regency. The majority of the population of Beurandeh village are farmers. Tobacco is the most commonly planted plant by the Beurandeh. Generally, tobacco is used as the basic ingredient of cigarettes, besides that tobacco is also widely consumed by older women as chewing tobacco. The problem that is often faced in the tobacco processing process is that it is still manual and old so it is less efficient. The purpose of this service is to provide training to the people of Beurandeh village to be able to use tobacco chopping machines properly, so that the time and energy to chop tobacco is more effective and efficient, and drying time is also completed faster. The method used in this service activity is in the form of direction and discussion between the speaker and the tobacco farming community. The result of this service is that the community can understand how to used a tobacco chopping machine so that time and energy are more efficient, and women who dry tobacco do not need to dryi up under the hot sun because the chopping process is completed faster.